Wireless Algorithms, Systems, and Applications 7th International Conference, WASA 2012, Yellow Mountains, China, August 8-10, 2012, Proceedings - Wang, Xinbing; Zheng, Rong; Jing, Tao; Xing, Kai (Theoretical Computer Science and General Issues, 2012)
This book constitutes the refereed proceedings of the 7th International Conference on Wireless Algorithms, Systems, and Applications, WASA 2012, held in Yellow Mountains, China, in August 2012. The 24 revised full papers presented together with 32 invited papers were carefully reviewed and selected from 116 submissions. The papers cover a wide range of topics such as cognitive radio networks, cyber-physical network systems, mobile handset networking systems, underwater and radar wireless networks, and wireless and mobile security.